The use of artificial intelligence in nephrology - Weronika Buczek; Mikołaj Wiśniewski; Rafał Oleszczuk; Iga Kozińska; Maciej Orczykowski (Kazimierz Wielki University, 2022)
Introduction and methods Artificial Intelligence(AI) is a relatively new branch of science that studies the display of intelligent behavior by machines and its use in advanced analysis and computation. Due to the potential use of AI, it has also been introduced into medicine and nephrology. The following article is an analysis of the current knowledge on the potential of AI in nephrology and its relevance to clinicians based on the latest publications contained in the PubMed and Google Scholar databases. Stage of knowledge AI found its application in the prognosis of the development of IgA nephropathy thanks to the use of a neural network, which by analyzing the results of research and the drugs used in a large group of patients has learned to detect patients at high risk of developing severe complications at the beginning of the disease. What is more, AI makes it possible to detect DKD earlier and delay renal replacement therapy. In patients undergoing hemodialysis, artificial intelligence developed a model that calculated the appropriate duration of the procedure and adjusted drugs to control blood pressure. Another example of the use of AI is its use in relation to patients undergoing kidney transplantation. The AI calculates the beneficial concentration of an immunosuppressive drug specifically for a given patient, which allows clinicians to limit adverse effects. Summary AI is a breakthrough technology that is constantly being developed. Despite the high cost of implementing this technology, it is believed that it could represent the future of medicine and be a new way in treatment techniques and in the early detection of diseases in nephrology.